Parametric bufferness in systems of parabolic and hyperbolic equations with small diffusion - Kolesov, A. Yu.; Mishchenko, E. F.; Rozov, N. Kh. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We investigate the problem of parametric excitation of oscillations in systems of parabolic and hyperbolic equations with small coefficient of diffusion. We establish the phenomenon of parametric bufferness, i.e., the existence of an arbitrary fixed number of stable periodic solutions for a proper choice of the parameters of equations.